1992: What is to be done?. (1st November 2020) - Clarke, Arthur C.
ABSTRACT: This time, the "unthinkable" could mean the end of nuclear weapons. Arthur C. Clarke kicks off the discussion. Clarke, best known as the author of 2001: A Space Odyssey, writes about how to re-purpose the financial and human resources that the world expended on the nuclear weapons race of the Cold War.